2018
DOI: 10.1038/micronano.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Whole-blood sorting, enrichment and in situ immunolabeling of cellular subsets using acoustic microstreaming

Abstract: Analyzing undiluted whole human blood is a challenge due to its complex composition of hematopoietic cellular populations, nucleic acids, metabolites, and proteins. We present a novel multi-functional microfluidic acoustic streaming platform that enables sorting, enrichment and in situ identification of cellular subsets from whole blood. This single device platform, based on lateral cavity acoustic transducers (LCAT), enables (1) the sorting of undiluted donor whole blood into its cellular subsets (platelets, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 45 publications
0
64
0
Order By: Relevance
“…Ward et al demonstrated that the percentage of sonoporated cells is proportional to the cubic power of the microbubblecell spacing. [59,60] Additionally, the air microbubble generated by the air/liquid interface without a shell used in this study can oscillate freely, making the sonoporation more efficient. By combining the secondary acoustic radiation force and the drag force induced by microstreaming, a single cell can be trapped at the microbubble surface at a trapping rate of up to 95.50 ± 2.78% (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…Ward et al demonstrated that the percentage of sonoporated cells is proportional to the cubic power of the microbubblecell spacing. [59,60] Additionally, the air microbubble generated by the air/liquid interface without a shell used in this study can oscillate freely, making the sonoporation more efficient. By combining the secondary acoustic radiation force and the drag force induced by microstreaming, a single cell can be trapped at the microbubble surface at a trapping rate of up to 95.50 ± 2.78% (Figure 5b).…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from (28), it is dependent on the bubble size, distance between the bubble centers, and damping factors of the bubbles. The dependence of non-dimensional (with respect to the resonant frequency of a single bubble) resonant frequency from the non-dimensional bubble radius (with respect to the distance between the bubble centers) is given in Fig.…”
Section: B Bubble Pairmentioning
confidence: 99%
“…3,[12][13][14][15] Other applications of oscillating bubbles to be mentioned are micropumps, 16 microtweezers, [17][18][19] microfilters, 20 microrotors, 21 biosensors, 22 microswimmers, [23][24][25] and sorting. [26][27][28] An extensive literature exists on theoretical predication of dynamics as well as resonant and dissipative behavior of spherical bubbles, capitalizing on the well-known Minnaert 29 frequency. The dynamics of spherical bubbles that are either free or confined inside a cavity has been studied for more than a century, starting from the seminal work of Rayleigh 30 and followed by Plesset 31 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, HTs trap particles in static immobilization and cannot selectively transport individual objects, preventing their further development for complex applications. Inspired by the hydrodynamic methods, streaming effect induced by optic‐heat, and acoustics has been explored to develop noncontact microrobots. Especially, acoustic streaming, which arises from the nonlinear propagation of a compression wave through an attenuating media, has been studied as a promising approach for micro/nano manipulation, since it can artificially induce fluid flow where velocity can be tuned independently of the flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D‐VSA is highly localized with rapid‐rotating velocity, enabling an excellent trapping capability for different sized particles ranged from micrometers to sub‐100 nm. Different from the planar vortices generated by acoustic bubbles or focused SAWs, the 3D‐VSA generated in the HSHT has a rotation axis parallel to the substrate, of which the formation can be well tuned with the applied flow rate, forming the basis for size‐selective trapping and multifunctional manipulations of micro/nanoscale objects. Meanwhile, under the viscous driving force, the trapped particles can be rotated at the equilibrium positions.…”
Section: Introductionmentioning
confidence: 99%